ANALISIS KINERJA DENGAN METODE ECONOMIC VALUE ADDED (STUDI KASUS PT. ASTRA INTERNATIONAL TBK ) (Riset Manajemen & Akuntansi, 2010)
Performance measurement can be utilized to assess the company efficacy and also as basis for compile the reward system in company. Performance measurement which is many used is ROA and also ROE will push the manager to avoiding investments in project to cause degrading again the investment though beneficial project, and risk lower. This is especial weakness at performance measurement ROA and ROE disregarding the existence of traditional performance above, so reached by the strategy alternative felt more perfect, that is with method EVA (economic value added). In this method profit operates for after interest and tax (EAT) lessened with Total cost capital (Total cost capital). So that EVA shows explicitly expense of company capital. Method EVA represents the process to maximize the company value